Geographic variation in the flavour volatiles of alphonso mango - Kulkarni, Ram S.; Chidley, Hemangi G.; Pujari, Keshav H.; Giri, Ashok P.; Gupta, Vidya S. (Food Chemistry, 2012)
Alphonso, one of the most popular cultivars of mango in India is known to exhibit geographic variation in the flavour of ripe fruits. To get chemical insight into this difference, volatiles were studied in the ripening fruits of Alphonso mangoes from three cultivation locations in India. Ripe fruits from Deogad had lower content of mono- and sesquiterpenes and higher content of lactones and furanones as compared to the fruits from Dapoli: whereas fruits from Vengurle had average quantities of these chemicals in comparison with Deogad and Dapoli fruits. This variation was clearly reflected as separate clustering of the localities in the Principal Component Analysis. The localities were indistinguishable from each other in terms of raw fruit volatiles. This study exemplifies a case of phenotypic plasticity; since the plants chosen were clonally propagated, such geographic variation in the volatiles can be attributed to varied abiotic conditions at these three localities. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Mango; Phenotypic plasticity; Ripening; Volatiles